ANALISIS AUDIT KEPATUHAN TERHADAP PROSEDUR PEMBERIAN PEMBIAYAAN MODAL KERJA PADA BANK SULSELBAR CABANG SYARIAH MAKASSAR - Abdul Khaliq (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2020)
This study aims to analyze compliance audit of the working capital financing procedure at Bank Sulselbar Makassar Sharia Branch. The method of analysis used in this research is qualitative analysis method. In this case, the researcher uses a risk-based audit approach, an audit approach which checks the harmony between the policies and the procedures performed by the regulations. Thus, Bank Sulselbar Makassar Sharia Branch must be in line with regulations or procedures that have been held by Bank Indo nesia (BI) in terms of financing. Based on the result of the research, it shows that the Compliance Audit conducted by Compliance Director and Compliance Unit of Bank Sulselbar Makassar Sharia Branch has been running well in accordance with its duties and authority and maintaining its independence well because it has work guidance, work system and procedures that have been referring to the provisions current regulation. Likewise in terms of providing working capital financing to customers has been in accordance with applicable procedures. All financing stages or procedures have been implemented or followed before financing decision can be realized. And each stage is not immune from the supervision of the Compliance Group so that any part or section concerned at that stage is professionally responsible.